Effectiveness of Implementing Complete Systematic Land Registration on Village Lands in Singakerta Village, Gianyar District - MATARAM, I Gede Arie; SUKANDIA, I Nyoman; UTAMA, I Wayan Kartika Jaya (Indonesia Strategic Sustainability, 2023)
The existence of customary land cannot be separated from the existence of a Traditional Village, for example, in Bali Province, where a Traditional Village has the right to own land called Druwe Village. The existence of Druwe Village has a starting point that is measured by the existence of traditional villages. Land has become an elemental philosophy, with the term Pateman, which is an element that creates a balanced life that is related to the continuity of environmental life. In this research, the discussion is about the effectiveness of carrying out village land registration through a complete system land registration (PTSL) program in Singakerta Village, which is located in Gianyar Regency and the rights and obligations of all traditional village members who live/occupy the land. Carried out from generation to generation after the village yard land (PKD) is registered. This research uses research conducted empirically. The Government's ongoing efforts to carry out land registration in regions in Indonesia, namely in the Singakerta Traditional Village, include carrying out improvements and implementing regulations so that they are perfect for the regulations that have been issued. About the issuance of a Land Certificate in the name of an individual or an individual regarding Tri Hita Karana objects, one of which is tebe/telajakan land, by submitting a personal land registration application using personal fees and if the budget year is for an object that is not designated by the systematic land registration object complete (PTSL).